Facies Architecture and Paleogeography of the Battfjellet Formation, Rypefjellet, Spitsbergen - Skarpeid, Silje Skorve (The University of Bergen, 2010)
The shallow marine sandstones of the Battfjellet Fm are part of a regressive mega-sequence that represent the last stages of infilling of the Paleogene Central Basin in Spitsbergen. The Battfjellet Fm is believed to be of Eocene age and was deposited in a foreland basin that developed in front of the West Spitsbergen Orogen, a fold-and-thrust belt that formed along the western coast of Svalbard as a response to the northward spreading of the opening of the Atlantic Ocean. The Battfjellet Fm has been interpreted to represent wave-dominated delta deposits that built out into the Central Basin in an easterly direction. The shoreline had a north-south orientation and rivers delivered sediments into the basin from a western source area. Sediments deposited by turbidite currents were deposited on the slope and basin-floor in the western parts of the basin. Hyperpycnal currents, possibly formed as a result of floods have been interpreted as important for the generation of turbidite currents although other processes such as storm-waves and tectonic movements also are capable of generating turbidity currents. The basin-floor topography is believed to have affected the distribution of the sands deposited in this area. The sandy basin floor turbidites were only deposited in the western parts of the Central Basin where the basin has been interpreted to have been deeper. The thicknesses of sediment also reflect this trend where thicker sediment packages are found closer to the orogen. These observations point to an asymmetric infilling of the basin. The shallow marine deposits of the Battfjellet Fm show that wave-action was important in the basin, and these deposits show a coarsening and shallowing upwards trend with mainly wave-generated deposits in the shoreface environment. These represent parasequences and the sandy sequences are capped by transgressive shales. The number of parasequences varies over short lateral distances in the study area and this has been interpreted to represent switching of delta lobes. Master i ...